2014
DOI: 10.1097/acm.0000000000000089
|View full text |Cite
|
Sign up to set email alerts
|

Gender Distribution of U.S. Medical School Faculty by Academic Track Type

Abstract: Medical schools offering the CET type reported higher proportions of female faculty on that track type. Given that faculty on the CET type lag behind their TTT colleagues in academic promotion, these findings may contribute to continued challenges in gaining academic and leadership parity for women in academic medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 40 publications
(49 reference statements)
0
80
0
Order By: Relevance
“…This explanation is likely reductionist and subsequently raises the question of why more men than women choose to pursue research careers. A 2011 study of gender and type of academic track [14] reported that 77 % of institutions offering a clinician-educator track had a higher proportion of female faculty on that track, whereas institutions offering a tenure track had a higher proportion of male faculty. Faculty on the clinician-educator track had lower rates of promotion than the tenure track faculty.…”
Section: Discussionmentioning
confidence: 98%
“…This explanation is likely reductionist and subsequently raises the question of why more men than women choose to pursue research careers. A 2011 study of gender and type of academic track [14] reported that 77 % of institutions offering a clinician-educator track had a higher proportion of female faculty on that track, whereas institutions offering a tenure track had a higher proportion of male faculty. Faculty on the clinician-educator track had lower rates of promotion than the tenure track faculty.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is continued reason for concern that this pipeline theory is not supported given the lack of increased numbers of women in senior leadership positions. 2,[11][12] Women continue to be lost at every academic transition in an academic career path. 2,27 Leadership development programs, including development programs, such as the American Dental Education Association's (ADEA) Leadership Institute and the Executive Leadership in Academic Medicine (ELAM), can make a difference.…”
Section: Discussionmentioning
confidence: 99%
“…While the concept of tenure continues to evolve and the importance of funding from clinical practice for faculty member lines grows, the slower rate of promotion of these non-tenure track positions affects women disproportionately more than men. 11 In academic medicine in 2012, women made up 20% of professors, 32% of associate professors, and 43% of assistant professors. 13 According to the National Science Foundation, among science, engineering, and health doctorate holders employed in universities and 4-year colleges, 21.9% of professors, 38% of associate professors, and 44.4% of assistant professors are women.…”
Section: Faculty Rank and Tenurementioning
confidence: 99%
See 2 more Smart Citations